Effect of family socio-economic status on subjective well-being among Norwegian adolescents: Mediation and moderation effects by general self-efficacy from a gendered perspective - Catherine Anne Nicole Lorentzen (BMC Public Health, 2025)
Abstract Background In order to better target public health interventions addressing socio-economic disparities in mental health among adolescents, a better understanding of this phenomenon is needed. This study aimed at investigating the mediating and moderating roles of adolescents´ general self-efficacy in the relationship between their family socio-economic status and their subjective well-being, and the dependence of these effects on gender. Methods The study was based on data from the 2021 cross-sectional Ungdata survey among 17,941 adolescents aged 14 to 19 in a Norwegian county. Four multivariable linear regression-based mediation/moderation analyses were conducted: a simple mediation model tested whether the effect of family socio-economic status on well-being was mediated by general self-efficacy, a moderated mediation model tested whether such a mediation effect was moderated by gender, a simple moderation model tested whether general self-efficacy moderated the effect of family socio-economic status on well-being, and a moderated moderation model tested whether such an interaction effect was moderated by gender. Results We found that some of the positive effect of the adolescents´ family socio-economic status on their well-being was mediated by their general self-efficacy beliefs. This indirect effect was stronger for girls than for boys due to the stronger positive association between general self-efficacy and well-being among girls. General self-efficacy also moderated the association between family socio-economic status and well-being, i.e. general self-efficacy slightly protected against reduced well-being among adolescents living in families with fewer socio-economic resources. This moderation effect was not dependent on gender. Conclusions These findings enhance our understanding of the pathways by which socio-economic status affects adolescent mental health and the factors that may protect against the negative influences of living in socio-economically less advantaged circumstances. From a public mental health perspective with particular focus on reducing inequalities in well-being among adolescents, it appears especially fruitful to support the strengthening of general self-efficacy beliefs among girls and among adolescents from lower socio-economic households.